TGF-beta: a master immune regulator. (3rd May 2020) - Larson, Christopher; Oronsky, Bryan; Carter, Corey A.; Oronsky, Arnold; Knox, Susan J.; Sher, David; Reid, Tony R.
ABSTRACT: Introduction : Transforming Growth Factor-Beta (TGF-β) is a master regulator of numerous cellular functions including cellular immunity. In cancer, TGF-β can function as a tumor promoter via several mechanisms including immunosuppression. Since the immune checkpoint pathways are co-opted in cancer to induce T cell tolerance, this review posits that TGF-β is a master checkpoint in cancer, whose negative regulatory influence overrides and controls that of other immune checkpoints. Areas Covered : This review examines therapeutic agents that target TGF-β and its signaling pathways for the treatment of cancer which may be classifiable as checkpoint inhibitors in the broadest sense. This concept is supported by the observations that 1) only a subset of patients benefit from current checkpoint inhibitor therapies, 2) the presence of TGF-β in the tumor microenvironment is associated with excluded or cold tumors, and resistance to checkpoint inhibitors, and 3) existing biomarkers such as PD-1, PD-L1, microsatellite instability and tumor mutational burden are inadequate to reliably and adequately identify immuno-responsive patients. By contrast, TGF-β overexpression is a widespread and profoundly negative molecular hallmark in multiple tumor types. Expert Opinion : TGF-β status may serve as a biomarker to predict responsiveness and as a therapeutic target to increase the activity of immunotherapies.